2000
DOI: 10.1159/000014480
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro Bacterial Touch Contamination Risk Assessment of Two CAPD Twinbag Systems

Abstract: The objective of this study was to compare, using in vitro quantitative microbiology, the ability of two commercially available peritoneal dialysis solution delivery systems to prevent and remove, via convective fluid flow, intralumenal fluid path bacterial contamination. The two systems (A and B) differed in both the configuration of their flow control, or Y-junction and the method of fluid flow control and also in the design of their Luer tubing connectors. System A had a tubing type Y-junction that requires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…PD transfer sets differ markedly between manufacturers, with studies consistently showing better elimination of potential bacterial contaminants by systems with controllers external to the flow path, rather than within the tubing. 43 A scoping systematic review by industry employees has shown that PD systems from different manufacturers have different PD peritonitis rates, 44 and this is a high priority for follow-through by independent investigators.…”
Section: Discussionmentioning
confidence: 99%
“…PD transfer sets differ markedly between manufacturers, with studies consistently showing better elimination of potential bacterial contaminants by systems with controllers external to the flow path, rather than within the tubing. 43 A scoping systematic review by industry employees has shown that PD systems from different manufacturers have different PD peritonitis rates, 44 and this is a high priority for follow-through by independent investigators.…”
Section: Discussionmentioning
confidence: 99%
“…Internet addiction is defined as, "an individual's inability to manage his or her use of the Internet, which finally results social, psychological, school, and/or work difficulties in a person's life" [20]. It is found that the university students may use the Internet addictively or Internet addiction adversely effects on individuals, physical health, family life, changing their social behavior, habits and abilities, and academic performance [6,14,[19][20][21][22][23]. In spite of the facts, Internet addiction was the first classified as a behavioral addiction and characterized as a form of cyber sexual addiction [24], cyber-relationship addiction [25], net compulsion [26], information overload [27], and addiction to interactive computer games [1,28].…”
Section: Introductionmentioning
confidence: 99%
“…Our results show that none of the bacteria contaminating the pin were transferred to the fluid path, ruling out the possibility of bacteria gaining access to the peritoneum during PD fluid exchanges. These results are all the more impressive considering the level of contamination generated by the challenge procedures (1.6x10 5 CFU), which is considerably higher than might be expected in the clinical setting—from 10 2 CFU by unprepared hands, up to 4.5x10 3 CFU if hands are washed but not dried (22)—or than has been reported as the worst-case touch contamination scenario in previous studies (23-25) evaluating the ability of several commercially available PD connectors to prevent fluid path contamination (Table 1).…”
Section: Discussionmentioning
confidence: 56%
“…32, NO. 5 PDI (22)-or than has been reported as the worst-case touch contamination scenario in previous studies (23)(24)(25) evaluating the ability of several commercially available PD connectors to prevent fluid path contamination (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation